Shariah Audit in Information Technology Systems for Buy Now Pay Later (BNPL) Platforms: A Study on Compliance, Governance and Implementation - Najma Athirah Mohammad Shafie; Zurina Shafii; Muhammad Ilyas Ariffin Abu Bakar (Fakulti Ekonomi dan Muamalat, 2025)
International Islamic Economic System Conference (I-iECONS 2025) "Digitalization, Innovation and Sustainable Development Through Islamic Economics"/ editors: Amalina Mursidi & Nur I'ffah Muhammad Nasir Organized by the Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM) Conference Dates: 26-31 August 2025